Kegagalan Penerapan Good Corporate Governance Pada Perusahaan Publik Di Indonesia - Djohari Santoso (Jurnal Hukum IUS QUIA IUSTUM, 2008)
This article aimed to study The Failure of Implementation of Good Corporate Governance (GCG) on Public Companies in Indonesia. Implementation GCG, specifically in public companies, is very important because it could enhanced corporate profit and shareholder gain in long term By using normative legal methods, this article demonstrated: First; GCG is a concept emphasizing the importance of the user right of financial statement to get the information accurately and timely; and the company management liability to provide the information accurately and perform the company fundamental value. Second; implementation GCG failed in Indonesia. It just because many public companies still hesitated to fully implement GCG. Third, Indonesia does not need more law. What is needed is a changed legal culture that will put to work these laws and institutions as they are designed to be used and commitment in every aspect of professional life to implement GCG.